IMPLEMENTATION OF THE TRIPLE HELIX MOHAMMAD NATSIR IN ARABIC EDUCATION IN STIBA ARRAAYAH - Rizal Firdaus; Kama Abdul Hakam; Momod Abdul Somad; Ahmad Syamsu Rizal (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The integration of mosque institutions, islamic boarding schools and campuses in the educational process according to Mohammad Natsir is very necessary. He believes that this concept is very in line with the culture of Indonesian society, according to him, the educational process that integrates the three institutions can make graduates become intellectually, emotionally and spiritually intelligent people. Arraayah College of Arabic Teaching (STIBA Arraayah) including one of the institutions that have successfully applied the concept in the field of Arabic language education. This is evident in his achievements in various Arabic language competitions and the interest of partner institutions in STIBA Arraayah graduates is very high. This success cannot be separated from the strategy and innovation that boils down to the integration of the three components of the institution in STIBA Arraayah, namely mosques, islamic boarding schools (pesantren) and campuses or college. This research uses qualitative techniques, data sourced from documentation studies and interviews, the data analysis techniques used are Miles and Huberman data analysis techniques, namely data analysis techniques consisting of three stages of analysis, namely collecting data and data reduction, display data and conclusion. The findings in this study are the implementation of Mohammad Natsir's triple helix at Arraayah University including 1) Implementation of Arabic language teaching in the Arraayah Mosque through ilqo kalimah activities (short speech), halaqoh of the Qur'an (tahfidz), mashrohiyyah (arabic theatrical), scientific competitions, 2) The implementation of Arabic language teaching at Pesantren Arraayah is carried out in various places such as in madrasahs through Arabic language learning activities, dormitories through study group activities, monitoring Arabic-language discipline, direct evaluation from the senior student, Arabic environtment conditioning, sports fields through Arabic-language conditioning activities in various sports activities, open spaces and in other public facilities in pesantren through activities jalsah tarbawiyyah; 3) The implementation of Arabic language teaching at the Arraayah Campus is carried out in lecture classes through learning materials for Arabic and Islamic studies as well as the development of Arabic language education through teaching practices and research in the Arabic Teaching Studies.